A look at the history of veterinary medicine - Xalimmetova Roxatoy Davlatbayevna (Genius Journals, 2023)
If the main problem for the Central Asian countries is the preservation of peace and tranquility in Afghanistan, then the next problem is climate change, which cannot but affect Uzbekistan. The world's media are spreading disturbing and sad news about forest fires in Siberia, Europe and America. All environmental changes and catastrophes in the world actually occur due to human fault, most floods are the result of global warming. Such problems create risks such as a shortage of clean drinking water and food. The leading role in protecting the population of our country from such problems is played by the field of veterinary medicine. This article analyzes the practical experience of the development of veterinary medicine in our country
Keywords: Central Asia; America; Afghanistan